Rancang Bangun Pengontrolan Arah Kincir Angin Sumbu Horizontal Menggunakan Motor Servo - Andri Minawal; Rahyul Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Windmills are a tool that can be used to convert kinetic energy in the wind into mechanical energy. The kinetic energy in the wind is in the form of translational energy which is converted into rotational energy and then it can also be used according to a need. Its main task is to convert wind energy into electrical energy, apart from that a windmill is also needed to be able to protect itself from the enormous ferocity of the wind. Protection is carried out at a windmill to prevent overspeed. If there is no protection system, the rotor will rotate to the limit of the capacity of a generator, blades and other rotor components so that it will malfunction and cause danger. In this study, a continuous rotation servo motor is used to control the direction of the windmill with a limited output voltage value. The prototype of this windmill was tested with a wind speed engineered using a fan as the direction of the wind. If the voltage value is below or above the output voltage value limit that has been programmed on Arduino, the servo motor on the windmill will rotate CW 90 °. If the output voltage value is within the normal range, the windmill does not rotate to receive the wind energy it receives. For the test results that have been carried out, the results obtained in the first test when the fan condition is Off, the windmill produces an output voltage of 0V and the windmill rotates CW 90 °. In the second test, when the fan is on, the windmill produces an output voltage of 2.25V, in a condition the windmill does not rotate. Then the fan starts off and produces an output voltage of 0.93V then the windmill rotates 90 ° CW. In the third test when the fan is on and after that the speed of the fan is increased to test the windmill so that it can rotate when getting the upper limit voltage value. When the fan is on, the windmill produces an output voltage of 2.61V on the gauge and the windmill does not rotate. Then the fan speed is increased and rotates CW 90 ° when it gets an output voltage of 3.36V. Keyword: Direction, Windmill, Control, Horizontal Axis, Servo Motor